(untitled) (ModaPalavra e-periódico, 2015)
Clothing, accessories and all kinds of adornment define, distinguish, determine and identify individuals according to their social, cultural and artistic sphere. The intention of this article is to pointing out the importance of cultural and social analysis of the garment through theoretical interaction the authors, with their own artistic, historical and cultural perspectives. As well as conceptualizethe terms "fashion", "costume", and "clothing" for understanding their relationships and social and cultural construction of their specific contexts. And besides, the search possibilities of analysis of perceptions of clothing in the form object, and whenit comes to their stylistic characteristics, visualelements and discourse. It is shown, then, how numerous spheres of knowledge aim at multidisciplinary and interdisciplinary discourses for the understanding and the study of a complex object, such as clothing, whose compositions signify and discuss on varied cultural, artistic, political and social positions.